Training and Assistance in Making Bokashi Fertilizer for Teachers in Polewali Mandar Regency, West Sulawesi - Musrifah Tahar; Ariandi Ariandi; Mesra Damayanti; Ayu Indayanti Ismail; Sufyan Hakim (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Dry leaves or grass in schools are generally thrown away or burned which has an impact on pollution and environmental pollution. Prevention of this pollution can be done by utilizing the dry leaves/grass into other products that are more useful. The Biology and Science Education Study Program Community Service implementation team in collaboration with the Polewali Mandar District Mobilizing Teacher Community provided training for teachers to be able to process dry leaves/grass in the surrounding environment into bokashi fertilizer. This community service aims to provide knowledge and skills to the community regarding the processing of dry leaves/grass into bokashi fertilizer. This activity was carried out by providing material and the practice of making bokashi fertilizer. Participants in the activity gave a positive response to the implementation of the activity. The results of the lesson indicate that the majority of the participants agreed that the lesson was in line with the topic and that the instructor was capable of providing materials and answering questions appropriately. In addition to that, participants agreed that the course increased the teacher's ability to transform dry leaves/grass in the schoolyard into bokashi fertilizer.